2016
DOI: 10.1172/jci.insight.86548
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal CYLD inactivation sensitizes mice to the development of sebaceous and basaloid skin tumors

Abstract: The deubiquitinase-encoding gene Cyld displays a dominant genetic linkage to a wide spectrum of skin-appendage tumors, which could be collectively designated as CYLD mutant–syndrome (CYLDm-syndrome). Despite recent advances, little is understood about the molecular mechanisms responsible for this painful and difficult-to-treat skin disease. Here, we generated a conditional mouse model with epidermis-targeted expression of a catalytically deficient CYLDm through K14-Cre–mediated deletion of exon 9 (hereafter re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
(64 reference statements)
0
16
0
1
Order By: Relevance
“…A strong CENPV expression was also observed in TE, a benign follicular tumor closely related to BCC and considered by some authors as a more differentiated state of the same entity. Interestingly, CYLD inactivation in mice was shown to promote the development of sebaceous and basaloid skin tumors (Jin et al, 2016). Moreover, we report that TEs and CYLs are highly ciliated tumors, similar to BCCs.…”
Section: Discussionmentioning
confidence: 66%
“…A strong CENPV expression was also observed in TE, a benign follicular tumor closely related to BCC and considered by some authors as a more differentiated state of the same entity. Interestingly, CYLD inactivation in mice was shown to promote the development of sebaceous and basaloid skin tumors (Jin et al, 2016). Moreover, we report that TEs and CYLs are highly ciliated tumors, similar to BCCs.…”
Section: Discussionmentioning
confidence: 66%
“…Instead, they need to be challenged with topical administration of chemicals before skin tumors appear, suggesting that Cyld-inactivation itself is not sufficient for tumorigenesis. Interestingly, a recent study indicate that specific inactivation of Cyld in K14-positive hair follicle and basal epidermal cells followed by topical challenge with DMBA and TPA results in development of sebaceous and basaloid tumors with some resemblance to BSSassociated tumors [12]. However, since there are no prior reports of established cell lines or xenografts of tumors from BSS patients, the present PDX model is thus the first preclinical model that truly recapitulates human inherited CYLD-defective cylindromas.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies of Cyld-defective mouse models have shown that they do not recapitulate the histological and clinical characteristics of BSS particularly well [11,12]. Thus, these mice do not spontaneously develop skin tumors mimicking cylindromas or spiradenomas.…”
Section: Discussionmentioning
confidence: 93%
“…A previous genome-wide geneexpression study revealed that maternal FA deficiency affected the expression level in the offspring of Cyld, which encodes a deubiquitinating enzyme. 11 Cyld was reported to present the genetic attributes of a tumor-suppressor gene, 20 and Cyld regulates keratinocyte differentiation and skin-cancer progression in human and mouse; [24][25][26] notably, in chemical-induced skin-tumor models developed using DMBA/TPA, Cyld-deficient mice were found to be susceptible to papilloma formation due to the acceleration of the NFκB signaling pathway. 25,26 Therefore, we examined Cyld expression at the mRNA and protein levels in the skin and tongue tissues of FA(þ) and FA(−) offspring: At P2, Cyld expression was approximately 38% and 60% lower in the skin of FA(−) offspring than FA(þ) offspring at mRNA and protein level, respectively (Fig.…”
Section: Maternal Fa Depletion Reduced Cyld Expression In Skin But Nomentioning
confidence: 99%
“…23 Especially in the skin, Cyld functions physiologically as a regulator of epidermal differentiation, 24 and its deficiency in the skin accelerates sensitivity to chemically induced skin-tumor development in mice. 25,26 In this study, we examined whether the effects of insufficient maternal FA consumption may induce squamous neoplasia (skin and tongue) in the offspring for the first time and test whether our novel assumption of this being mediated by Cyld is correct or not, using mouse model.…”
Section: Introductionmentioning
confidence: 99%